International handbook of selection and assessment (West Sussex : John Wiley & Sons, 1997)
This is a book for human resource professionals, academics, researchers and independent consultants who are engaged in assessing other people at work. It places assessment in its political, economic, social and organizational context, and provides a critical guide to emergent issues in both research and practice. The contributors to the book originate from countries in Europe, North America and Asia and provide a vital perspective for the rapid international developments in selection and assessment in the 1990s and beyond.
Downsizing and Deselection (P. Jackson)
Bibliografija uz svako poglavlje
Kazala
Keywords: profesionalna selekcija; psihologija rada; psihologijsko testiranje; zaposlenici